Saving Iraq rebuilding a broken nation - Kirdar, Nemir (Weidenfeld & Nicolson, 2009)
In his passionately argued book, Nemir Kirdar inspires hope that Iraq can be rebuilt and can start to generate peace and prosperity in a conflict-prone region. Born in Iraq, he draws on recollections of his early life and shows how, in times past, the country was able to rise above the diverse composition of its population.